2018
DOI: 10.18316/recc.v22i3.3963
|View full text |Cite
|
Sign up to set email alerts
|

Coming out in the classroom: still an occupational hazard?

Abstract: Abstract:In 2002, Russ, Simonds, and Hunt reported that coming out in the classroom was hazardous to gay instructors in the United States. We replicated their study in the same medium-sized North American university with a sample of 222 college students (71.7% White, 53.2% women, mean age = 19.66) who listened to a talk by a male speaker. Unknown to these students, we experimentally manipulated the sexual orientation of the speaker. In one section of a general education course, the speaker mentioned three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(21 reference statements)
0
7
1
Order By: Relevance
“…In a more recent study, DeSouza and Olson (2018) found similar results: Students in the straight instructor condition provided more favorable character ratings than those in the gay instructor condition, and students rated the gay instructor significantly lower on two of six prompts related to competence. In contrast, Boren and McPherson (2018) found students rated a gay instructor higher, but only for the caring dimension.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…In a more recent study, DeSouza and Olson (2018) found similar results: Students in the straight instructor condition provided more favorable character ratings than those in the gay instructor condition, and students rated the gay instructor significantly lower on two of six prompts related to competence. In contrast, Boren and McPherson (2018) found students rated a gay instructor higher, but only for the caring dimension.…”
mentioning
confidence: 60%
“…Because competence is a component of teacher credibility (Gili, 2013; Hendrix, 1993; McCroskey et al, 1974; Pornpitakpan, 2004; Teven & Katt, 2016), we sought to establish the lecturer’s subject-matter expertise by having him perform a musical work during the lecture. Promoting the highest possible credibility scores for a lecturer is in keeping with the procedures used by other credibility researchers (Boren & McPherson, 2018; DeSouza & Olson, 2018; Russ et al, 2002).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this instance, Karin’s sharing about her private life had a positive outcome; however, it is also possible that her credibility with other students may have been compromised. Researchers have discovered, for example, that disclosing a same-sex partner in the higher education classroom may have a negative impact on teacher evaluations (De Souza & Olson, 2018; Russ et al, 2002).…”
Section: Resultsmentioning
confidence: 99%